COMPARATIVE FACTOR ANALYSIS OF E-LEARNING AND GOOGLE SITES ADOPTION AS FINAL PROJECT INFORMATION PORTALS USING TAM - Catharina Adinda Mega Cahyani; Pramono, Terrence; Aldi Satria Mahotma, I Putu; Hidajat, Calvin Chandra; Lim, Alex Sander; Soekamto, Yosua Setyawan (ZONAsi: Jurnal Sistem Informasi, 2023)
Final Project is a scientific project that is structured based on the application of science and technology. For now, information about the final project can be accessed on the e-learning website. However, several problems were found in the use of e-learning as a source of information regarding the final project. For example, information regarding the final project must be re-uploaded every year even though there is a course that is similar to the final project course in the previous semester. Departing from the problems above, lecturers at the Faculty of Information Technology, Ciputra University finally made new innovations. The innovation is to build a static website to access information about the final project. The website uses Google Sites. This study uses the TAM (Technology Acceptance Model) analysis method. The author conducted a survey about the website usage to the students in the Program from the class of 2016 to 2019. The sampling method used was purposive sampling. Purposive sampling was used in this study because the researchers needed specific respondents, namely SIFT students who had taken the final assignment course. This study uses the regression model to analyze the relationship between intention to use and other constructs in the adoption of e-learning as an information portal for the Final Project. Researchers use the regression model on the adoption of e-learning and google sites. The model gets a value of 0.852 and 0.905 respectively.